(untitled) (Journal Of Educational and Psychological Researches, 2022)
Anger is one of the problems of scientific importance that psychologists and education scientists are interested in, especially societies and educational environments, because if a child’s anger continues to develop into violence, then it becomes an unusual behavior, and an indication of the child’s lack of adaptation to his family and his environment (Moses, 2013: 4) The outward expression of anger can be found in facial expressions, body language, physiological responses, and sometimes in public acts of human aggression or from wild animals (Desmond, 1967: 34) The current research aims to identify: • Measuring anger among kindergarten children. In order to achieve the aims of the research, the researcher built an anger measure to measure anger in kindergarten children, and it consists of three areas, first area: (the subjective emotional aspect) from item (1) to item (11), and the second area: (the physiological aspect) from item (12) to item. (19), the third area: (the apparent, external aspect) from item (20) to item (31). The total number of the anger measure in all its areas is (31) items, the teacher answer it ,the measure were presented to a group of arbitrators of experts and specialists in educational and psychological sciences, measurement and evaluation, kindergartens and fine arts of 18 experts to demonstrate the validity of the measure items and their suitability for children. The researcher extracted the apparent validity of the measure. The researcher extracted a number of psychometric properties of the measure by using the T-test for two independent samples (T-test) and the Pearson correlation coefficient, and the Chi-square test and the Kolmogrove - Smirnov. As for the stability, it was extracted by retest method (0.95) and stability Alpha Cronbach of (0.97). The research found that kindergarten children suffer from a state of anger... Based on these results, of anger... Based on these results; the researcher reached a number of appropriate recommendations and suggestions.